Pre‐ and postzygotic mechanisms preventing hybridization in co‐occurring species of the Impatiens purpureoviolacea complex. Issue 23 (24th November 2021) - Abrahamczyk, Stefan; Jandová, Michaela; Líblová, Zuzana; Janssens, Steven B.; Dostálek, Tomáš; Holstein, Norbert; Fischer, Eberhard
Abstract: In the species‐rich genus Impatiens, few natural hybrids are known, even though closely related species often occur sympatrically. In this study, we aim to bridge the gap between micro‐ and macro‐evolution to disentangle pre‐ and postzygotic mechanisms that may prevent hybridization in the Impatiens purpureoviolacea complex from Central Africa. We analyzed habitat types, species distribution, pollination syndromes, pollinator dependency, genome sizes, and chromosome numbers of seven out of the ten species of the complex as well as of one natural hybrid and reconstructed the ancestral chromosome numbers of the complex. Several species of the complex occur in sympatry or geographically very close to each other. All of them are characterized by pre‐ and/or postzygotic mechanisms potentially preventing hybridization. We found four independent polyploidization events within the complex. The only known natural hybrid always appears as single individual and is self‐fertile. But the plants resulting from self‐pollinated seeds often die shortly after first flowering. These results indicate that the investigated mechanisms in combination may effectively but not absolutely prevent hybridization in Impatiens and probably occur in other genera with sympatric species as well. Abstract : Several species of the complex occur in sympatry or geographically very close to each other. All of them are separated by pre‐ and/or postpollination hybridization barriers. We found four independent polyploidization events within the complex.